Prospek dan Tantangan Perkembangan Asuransi Syariah di Indonesia - Herry Ramadhani (Al-Tijary, 2015)
This paper wants to explore more about the prospects and challenges of the development of Islamic insurance in Indonesia. Islamic insurance industry in Indonesia has very good prospects for growth, the demand for insurance products based on shariah will continue to increase. This is supported by a large population of Indonesia and also as the largest Muslim country in the world. However, this industry will also experience a very strong obstacle because of the global economic downturn, as it also conditions the people are not educated about insurance, the free market has begun to be applied, resources are less about Islamic insurance, lack of capital and other on.Therefore it needs the government's role to help to continue to grow, with regulations that support this industry